Exploring The Advantages and Obstacles of Mobile Governance in Kashmir a Comprehensive Study - Dar, Showkat Ahmad (Green Publisher Indonesia, 2023)
Mobile governance (m-Governance) has emerged as a new paradigm for governance in many countries, including India. This study investigates the benefits and barriers of m-governance in the context of Jammu and Kashmir. The study used an analytical and documentary method to reach at conclusion. The findings suggest that m-governance has the potential to enhance citizen engagement and participation, increase transparency and accountability, and improve service delivery. The study also highlights several barriers that hinder the effective implementation of m-governance, including the lack of technological infrastructure and expertise, low literacy rates, and limited access to mobile devices and network connectivity, particularly in rural areas. Furthermore, the study identified concerns related to data privacy and security as a significant challenge to the adoption of m-governance. The study recommends that policymakers should take a holistic approach to m-governance by addressing the barriers and challenges while leveraging the benefits of mobile technology. The study recommends that the government should prioritize the establishment of technological infrastructure, providing digital literacy programs, and strengthening data protection laws to address citizens' privacy concerns. The study concludes that m-governance has the potential to transform the governance landscape in Jammu and Kashmir by improving transparency, accountability, and service delivery, but it requires a collaborative effort from policymakers, government officials, citizens, and private stakeholders to overcome the barriers and harness its full potential.